Emphasizing the Intrinsic Purpose of Public Administration: A Way Out of the Identity Crisis? - Lars Karlsson; Angelica Börjesson (Revue Gouvernance, 2017)
There is a long-standing discussion, often framed in terms of a crisis, in the literature about the identity of public administration. One of the most salient roots of this alleged crisis is the ideological and political questioning of the role of public administration. We argue in this paper that a way of strengthening the identity of public administration is to reconnect to the fundamental question of its purpose. In order to answer this question, we explore the concept of purpose and relate it to the philosophical and political theoretical discussions about the purpose of the state. We find two kinds of purposes, which we term the instrumentalistic and the intrinsic. If public administration is assigned an intrumentalistic purpose, it is assessed as valuable if the consequences are valuable. If it is assigned an intrinsic purpose, it is assessed as valuable in itself. We conclude that the instrumentalistic purpose of public administration dominates contemporary discourse, and that this contributes to the identity crisis. The article ends with a suggestion that the intrinsic purpose of public administration be given a more salient position in the discussion.